LncRNA OIP5-AS1 suppresses lung adenocarcinoma progression and modulates macrophage polarization through the miR-429/DOCK4 regulatory axis - Liu, Yihan; Wang, Yuhua; Cui, Long; Li, Runze; Xiao, Dan (Frontiers in Pharmacology, 2025)
BackgroundMacrophage polarization plays a pivotal role in shaping the tumor microenvironment and influencing cancer progression. Long non-coding RNAs (lncRNAs) have emerged as important regulators of this process. This study investigated the role of lncRNA OIP5-AS1 in lung adenocarcinoma (LUAD) progression and its involvement in macrophage polarization.MethodsThe expression of OIP5-AS1 in LUAD tissues and its association with patient prognosis were analyzed. Functional assays, including cell proliferation, migration, invasion, and cell cycle analysis, were conducted in LUAD cell lines. Bioinformatics prediction, luciferase reporter assays, and RNA immunoprecipitation (RIP) were used to explore the interaction among OIP5-AS1, miR-429, and DOCK4. Macrophage polarization and migratory capacity were assessed following manipulation of OIP5-AS1, miR-429, and DOCK4 expression.ResultsOIP5-AS1 expression was significantly decreased in LUAD tissues and associated with poor survival. Overexpression of OIP5-AS1 inhibited LUAD cell proliferation, migration, and invasion, induced G1 phase arrest, and suppressed tumor growth in vitro. Mechanistically, OIP5-AS1 functioned as a molecular sponge for miR-429, regulating DOCK4 expression. Overexpression of miR-429 or knockdown of DOCK4 reversed the effects of OIP5-AS1 on macrophage polarization markers and restored macrophage migration.Conclusion:OIP5-AS1 modulates macrophage polarization through the miR-429/DOCK4 axis and inhibits LUAD cell progression. This regulatory pathway may influence the tumor immune microenvironment and represent a potential therapeutic target in LUAD.